SEX WISE REGRESSION ANALYSIS FOR BRAN LENGTH - BRAIN WEIGHT RELATIONSHIP N TELEOSTS - SHERLY, P.S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2010)
Sex wise regression analysis of brain length-brain weight relationship in eight species of teleost were analysed to find out any variation in regression coefficients between males and females. The regression analysis shows a striking sex wise variation in most of the fishes. The regression coefficient is higher in females whereas the males of those fishes show a negative regression coefficient.